Causal effects between gut microbiota and IgA nephropathy: a bidirectional Mendelian randomization study - Ren, Feihong; Jin, Qiubai; Liu, Tongtong; Ren, Xuelei; Zhan, Yongli (Frontiers in Cellular and Infection Microbiology, 2023)
Background Therapeutic approaches that target the gut microbiota (GM) may be helpful in the potential prevention and treatment of IgA nephropathy (IgAN). Meanwhile, relevant studies demonstrated a correlation between GM and IgAN, however, these confounding evidence cannot prove a causal relationship between GM and IgAN. Methods Based on the data from the GM genome-wide association study (GWAS) of MiBioGen and the IgAN GWAS data from the FinnGen research. A bi-directional Mendelian randomization (MR) study was performed to explore the causal relationship between GM and IgAN. We used inverse variance weighted (IVW) method as the primary method to determine the causal relationship between exposure and outcome in our MR study. Besides, we used additional analysis (MR-Egger, weighted median) and sensitivity analysis (Cochrane’s Q test, MR-Egger and MR-PRESSO) to select significant results, followed by Bayesian model averaging (MR-BMA) to test the results of MR study. Finally, a reverse MR analysis was conducted to estimate the probability of reverse causality. Results At the locus-wide significance level, the results of IVW method and additional analysis showed that Genus Enterorhabdus was a protective factor for IgAN [OR: 0.456, 95% CI: 0.238-0.875, p=0.023], while Genus butyricicoccus was a risk factor for IgAN [OR: 3.471, 95% CI: 1.671-7.209, p=0.0008]. In the sensitivity analysis, no significant pleiotropy or heterogeneity of the results was found. Conclusion Our study revealed the causal relationship between GM and IgAN, and expanded the variety of bacterial taxa causally related to IgAN. These bacterial taxa could become novel biomarkers to facilitate the development of targeted therapies for IgAN, developing our understanding of the “gut-kidney axis”.